Persuasive Communication in Business Negotiations: Strategies and Techniques - Siagian, Erwin Iriyanto; Nurkarim, Muhammad Cesar; Maharani, Nadia (Ilomata International Journal of Social Science, 2024)
In the realm of business negotiations, persuasive communication stands as a cornerstone for achieving favorable outcomes. It involves the strategic use of language, body language, and emotional intelligence to influence counterparts towards mutually beneficial agreements. Understanding the nuances of persuasive communication in this context is crucial for navigating the complexities of modern business interactions. This study aims to explore the strategies and techniques of persuasive communication in business negotiations, with a focus on understanding its underlying principles, practical applications, and impact on negotiation outcomes. Through a comprehensive review of existing literature, the study seeks to identify key trends, challenges, and opportunities in the field, providing insights for practitioners and researchers alike. The research methodology employed in this study is a thorough literature review conducted using NVivo, a qualitative analysis software. Relevant sources including books, academic journals, articles, and reports were collected and analyzed to gain insights into persuasive communication strategies in business negotiations. The data collected were systematically analyzed to identify recurring themes, patterns, and relationships, providing a rich understanding of the subject matter. The study findings reveal a myriad of persuasive communication strategies and techniques employed in business negotiations, ranging from linguistic tactics to nonverbal cues and emotional appeals. Key themes identified include the importance of building rapport, understanding counterpart motivations, and adapting communication approaches to suit diverse cultural contexts. The implications of this study extend to both practitioners and researchers in the field of business negotiations. Practitioners can gain valuable insights into effective communication strategies, enabling them to navigate negotiations with confidence and finesse.